THE INFLUENCE OF WORK MOTIVATION, MASTERY OF INFORMATION TECHNOLOGY AND COMPETENCY ON EMPLOYEE PERFORMANCE AT THE OFFICE OF THE MINISTRY OF RELIGION, PASAMAN - Sari, Ria Widhia; Endarwita, Endarwita (Institut Teknologi dan Ilmu Sosial Khatulistiwa, 2024)
This research aims to examine the influence of Work Motivation, Mastery of Information Technology and Competence on Employee Performance at the Pasaman Regency Ministry of Religion Office. The population in this study were employees of the Ministry of Religion of Pasaman Regency, consisting of 38 people. This research sample used the Saturated Sampling technique. This research was analyzed using multiple linear regression. The results of the research show that work motivation has no significant effect on employee performance at the Pasaman Regency Ministry of Religion Office with a significance value of 0.112. Mastery of Information Technology partially has a significant effect on Employee Performance at the Pasaman Regency Ministry of Religion Office with a significance value of 0.001 and Competency has a significant effect on Employee Performance at the Pasaman Regency Ministry of Religion Office with a significance value of 0.004. Simultaneously, Work Motivation, Mastery of Information Technology and Competency have a significant effect on Employee Performance at the Pasaman Regency Ministry of Religion Office with a significance value of 0.000. From the Coefficient of Determination Test Results (R2), a value of 0.556 was obtained, meaning that Work Motivation, Mastery of Information Technology and Competency were able to contribute 55.6% to Employee Performance at the Pasaman Regency Ministry of Religion Office. Keywords: Work Motivation, Mastery of Information Technology, Competency and Performance